Indigenous Agency and Written Culture in the Jesuit Missions of Paraguay - Wilde, Guillermo Luis (2015)
Recent research has paid special attentionto the role played by indigenous elite in the production of texts and maps. Thediscovery of a large number of manuscripts made by indigenous authorities indifferent media and for diverse purposes, from council documents to personal accounts,calls into question old assumptions about indigenous passivity in the JesuitMissions. Evidence indicates that the skill of writing was important in the missions daily life, and that its practice was widespread among members of the indigenouselite. This article briefly explores some examples.